(untitled) (KYAMC Journal, 2018)
Background: To determine the mean bioavailability of cisplatin at different time interval after intravenous administration of cisplatin of 18-60 years old 50 male Bangladeshi cancer patients. Materials & Methods: Pharmacokinetic and demographic data were collected from 50 various types of male cancer patients received injection cisplatin 50 mg/m2 infusion for over 3 hours every alternate week for 3 weeks and mean population bioavailability were determined. Results: Statistical analysis from data of HPLC reported that the highest mean plasma concentration of cisplatin was found 428.32 μg/dl (±6.092) after 3 hours and highest mean urinary concentration of cisplatin was found 996.56μg/dl (±1.97) after 12 hours (P<0.05). Highest and lowest concentration of four suspected metabolites (CM2, CM3, CM4 and CM5) were identified in blood and corresponding urine with their specific RT (retention time) and Area (P<0.01) which suggestive of previous work. Conclusion: Following I/V administration plasma concentration of cisplatin at different time interval determined the proper dosing dosing interval of the drug and reduce toxicity. KYAMC Journal Vol. 9, No.-3, October 2018, Page 110-114